Introduction - Abu Zahrim, Yaser; Junidah, Lamaming (CRC PRESS, 2023)
Cellulose, as the main biopolymers derived from either wood or lignocellulosic materials, can be utilized in diversified products in various applications, including the energy, food and beverage industries, pharmaceutical and biomedical fields, pulp and paper industries, electric and electronic industries, as well as construction. In a report on the cellulose market, Pulidindi and Prakash of Future Business Insights (2022) estimated that the market was worth USD 219.53 billion in 2018 and that it would expand by 4.2% between 2018 and 2026 to reach USD 305.08 billion. Growing consumer demand and the development of cellulose usage and its derivatives boost increased production. Technology and engineering evolution have prompted the advanced development of new methods, inventions as well as new products which are greener and more sustainable. For example, food and beverage applications are being driven by rising demand for processed foods such as ready-to-eat meals and bakery products. Furthermore, a shift in consumer preference for plantbased ingredients in personal care and cosmetics is spurring market product development. This has led to the introduction and usage of sustainable non-wood-based alternatives made from agricultural waste. This lignocellulosic biomass includes oil palm fibers, rice husks and stalks, banana stems, bamboo, corn stalks, walnut shells, kenaf, bagasse, hemp fibers, and others.